Diabetes Mellitus and History of Tuberculosis Treatment as Risk Factors of Developing Multidrug-Resistant Tuberculosis at TB Polyclinic Dr. Soetomo General Hospital 2019 - 2020 - Muhammad Raihan Habibi; Arief Bakhtiar; Danti Nur Indiastuti; Resti Yudhawati Meliana (Universitas Batanghari Jambi, 2022)
Multidrug-Resistant Tuberculosis (MDR TB) is a condition when Mycobacterium tuberculosis were resistant to Isoniazid and Rifampicin simultaneously, with or without being followed by other first-line Anti-Tuberculosis Drugs. Diabetic patients who also have TB are more susceptible to drug resistance. There is ample evidence noting that a history of previous TB treatment is one of the main factors contributing to the development of MDR TB. This study was a case-control study. The sample of this study was all patients from TB Polyclinic Dr. Soetomo Hospital who were diagnosed with pulmonary TB by pulmonologists on January 1, 2019 – December 31, 2020, who met the inclusion criteria. The data obtained were analyzed using the IBM SPSS Statistics 23 application with a binary logistic regression test.There were 178 samples of this study. MDR TB (65.8%) was the dominant resistance type in Drug-Resistant Tuberculosis (DR TB) patients. Patients with DM were 2.2 times more likely to develop MDR TB than patients without DM. Patients with histories of previous tuberculosis (TB) treatment tended to be three times more likely to develop MDR TB than new patients. Other factors such as age, sex, BMI, history of alcohol consumption, and history of smoking did not show a significant relationship with the incidence of MDR TB. Diabetes Mellitus comorbidity and history of previous Tuberculosis treatment were significant risk factors for developing MDR TB.